Urgensi Peta Pengetahuan bagi Pengembangan Organisasi - Miftahus Saadah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
Recently, the discussion on knowledge management particularly on the field of knowledge map has received considerable attention among theorists and pratitioners of management. Knowledge map has been considered as important tool to improve organization performance as it provides thorough pictures of organization assets, either the tangible or the intangible resources. This article attempts to discuss the significance of knowledge map implementation within organization by firstly defining knowledge and knowledge map, and then the “who” of knowledge map, the underlaying assumption of knowledge map creation, the technology of knowledge map, the dynamic knowledge map, and lastly knowledge map in academic world. It is concluded that knowledge map is an overarching device urgently needed by organization including academic institutions.